Lawyers and the “new extraction” in Africa - (:unkn) unknown (My University, 2019)
Purpose The purpose of this paper is to examine the ongoing “new extraction” on the African continent. Contrary to mainstream scholarship and policies that see in law an external variable to remedy the “resource curse,” this paper channels attention toward the role of law as an institution of extraction in the longue durée . Unpacking the close association of law with the conversion of economic surpluses and power into enduring social relationships can help trace the mechanisms by which the uneven and unequal connection between Africa and the world is being negotiated, justified and challenged over time. Design/methodology/approach To this end, this paper deploys an approach anchored in political sociology of law and focuses on the roles played specifically by lawyers to trace the “interconnectedness” between European colonialism on the continent and the consolidation of the contemporary international economic and legal political order. It illustrates this approach with the case study of the “Africa” Bar in Paris as a key site in which extractive deals between multinational corporations and Francophone African states are negotiated. Findings This micro focus helps to explain the dual position of the “Africa” Bar in Paris, as offshore yet connected as it is shaped by both imperial legacies and ongoing waves of globalization into the African continent. Originality/value This approach traces a more nuanced explanation of Africa’s unequal and uneven relationship with the global economy as one shaped by the path of imperial legacies and successive and interconnected waves of globalization across Africa.
Keywords: African Research